FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU IBU DALAM PEMBERIAN IMUNISASI DASAR LENGKAP (IDL)PADA BALITA DI PUSKESMAS KOTO GASIB KABUPATEN SIAK - Alhidayati; Risa Amalia; Syukaisih; Yessi Rilovita (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2024)
Basic immunization is a form of effort to prevent infectious diseases to improve the quality of life. There are many factors that cause mothers to be unwilling to immunize their babies, namely internal factors such as lack of information, knowledge and maternal attitudes. Apart from internal factors, external factors also influence the provision of immunizations to toddlers, such as family support, access to services, the role of officers, culture and others. This study aims to determine the factors related to maternal behavior in providing complete basic immunization (IDL) to toddlers. This type of research is quantitative with a cross sectional research design. The population is 472 mothers with toddlers and a sample of 98 people. The sampling technique is cluster sampling. This type of data collection uses primary data, where this activity is carried out directly by distributing questionnaires and primary data. Data analysis is carried out univariately and bivariately using the Chi Square test. There is a relationship between knowledge, attitudes, information media, family support, access to services and the role of officers with providing complete basic immunization to toddlers (p.value <0,05). It is hoped that the Community Health Center will provide information in the form of counseling to mothers of toddlers about immunization with the aim of increasing the complete basic immunization coverage program for toddlers.